2023
DOI: 10.3389/fphar.2023.1271435
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin V regulates cell cycle progression and histone stability in the nucleus of breast cancer cells

Naphannop Sereesongsaeng,
James F. Burrows,
Christopher J. Scott
et al.

Abstract: Introduction: We previously identified that Cathepsin V (CTSV) expression is associated with poor prognosis in ER+ breast cancer, particularly within the Luminal A subtype. Examination of the molecular role of the protease within Luminal A tumours, revealed that CTSV promotes tumour cell invasion and proliferation, in addition to degradation of the luminal transcription factor, GATA3, via the proteasome.Methods: Cell line models expressing CTSV shRNA or transfected to overexpress CTSV were used to examine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been found that cathepsin L2 can also drive the progression of lung cancer by influencing the immunosuppressive environment and the cleavage of adhesion molecules ( 47 ). Furthermore, the activity of cathepsin L2 has been demonstrated to govern the advancement of the cell cycle and maintain the stability of histones within the nucleus of malignant cells found in breast cancer ( 49 ). It is also closely associated with the prognosis of HCC and the tumor microenvironment ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been found that cathepsin L2 can also drive the progression of lung cancer by influencing the immunosuppressive environment and the cleavage of adhesion molecules ( 47 ). Furthermore, the activity of cathepsin L2 has been demonstrated to govern the advancement of the cell cycle and maintain the stability of histones within the nucleus of malignant cells found in breast cancer ( 49 ). It is also closely associated with the prognosis of HCC and the tumor microenvironment ( 50 ).…”
Section: Discussionmentioning
confidence: 99%